Relative Distribution and Conservation of Genes Encoding Aminoglycoside-Modifying Enzymes in Salmonella enterica Serotype Typhimurium Phage Type DT104 - Frana, Timothy S. (American Society for Microbiology, 2001)
PCR was used to identify genes encoding aminoglycoside-modifying enzymes in 422 veterinary isolates of Salmonella enterica serotype Typhimurium. The identities of extra-integron genes encoding resistance to streptomycin, gentamicin, kanamycin, and apramycin were evaluated. Gentamicin resistance was conferred by the aadB gene. Kanamycin resistance was encoded by either the aphA1-Iab gene or the Kn gene. Apramycin resistance was determined by the aacC4 gene. Analysis of gene distribution did not reveal significant differences with regard to phage type, host species, or region except for the Kn gene, which was found mostly in nonclinical isolates. The data from this study indicate that pentaresistant DT104 does not acquire extra-integron genes in species- or geography-related foci, which supports the hypothesis that clonal expansion is the method of spread of this organism.